Anteseden dari E-Commerce User Satisfaction - Reva Vebria Oliviana (Peneliti.net, 2023)
The purpose of this study is to analyze the effect of quality system, information system, service and product quality, and delivery service have a positive effect on e-commerce user satisfaction. The sampling method used is purposive sampling with a sample 200 respondents who are users of e-commerce applications such as Shopee. The results of this study statethere is a positive effect on the quality of system, information, delivery service, and services on e-commerce user satisfaction, and product quality have no effect with e-commerce user satisfaction.